A food demand system based on demand for characteristics: if there is curvature in the Slutsky matrix, what do the curves look like and why?" - Bouis, Howarth E. (International Food Policy Research Institute, 1995)
A food demand system is proposed, based on demand for energy, variety, and tastes of foods. By specifying utility as an explicit function of these characteristics, the entire matrix of demand elasticities can be derived for n foods and one nonfood from prior specification of just four elasticities, while avoiding any assumption of separability between foods. This framework can explain why poorest groups often are most price-responsive, but also can account for highest price-responsiveness by middle income groups. The system is applied to published food consumption data for urban and rural populations in Pakistan. Elasticities are compared with those obtained in a published Pakistan study applying an almost ideal demand system (AIDS).